Effect of Sodium Chloride on Some Biological Aspects of Crustacean's Animal of Acanthocyclops bicuspidatus (Claus)(Copepoda: Cyclopoida) - Sadeq, SH. A.; Bassat, S.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present research includes the effect of different concentrations of NaCl on some biological aspects (longevity, growth and molting) of Acanthocyclops bicuspidatus (Copepoda; Cyclopoida).           The results showed a decrease of longevity with the increase of salt concentrations. The lowest mean of maleâ€²s longevity was 6.8 day in the 2ppt concen. compared with the control treatment 34.2 day, The lowest mean of femaleâ€²s longevity was 5.1 day in the 2ppt concen. compared with the control treatment 30.1 day.             The mean growth for males was lower than the mean growth of females. In males the lowest mean was 0.33mm in the 2ppt concen. compared with the control treatment 0.57mm, while in females was 0.36mm in the 1ppt and 2ppt concen. compared with the control treatment 0.62mm.            The mean number of molts decreased gradually with increasing concentrations. It reached 1 molt/male in the 2ppt concen. compared with the control treatment 5.7 molt/male, while in females was 1.6 molt/female in the 1.5ppt concen. and no molts in the 2ppt concen. compared with the control treatment 4.9 molt/female.